2(9x+1)+7(x-6)=60

Simple and best practice solution for 2(9x+1)+7(x-6)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(9x+1)+7(x-6)=60 equation:


2(9x+1)+7(x-6)=60

We simplify the equation to the form, which is simple to understand
2(9x+1)+7(x-6)=60

Reorder the terms in parentheses
+(+18x+2)+7*(x-6)=60

Remove unnecessary parentheses
+18x+2+7+*(+x-6+)=+60

Reorder the terms in parentheses
+18x+2+(+7x-42)=60

Remove unnecessary parentheses
+18x+2+7x-42=+60

We move all terms containing x to the left and all other terms to the right.
+18x+7x=+60-2+42

We simplify left and right side of the equation.
+25x=+100

We divide both sides of the equation by 25 to get x.
x=4

See similar equations:

| -2m-16=-51+3m | | ln(x)-ln(12)=0 | | 1-6k-6=-11 | | 18x+(-8)=-20+12x | | 11w=7260 | | 8(x-9)+3=-69 | | xsquared-4x+3=0 | | 2(7-2x)=-3(x-7) | | -9+5y=2 | | 7(x-2)+7=5x+2(-1+x) | | 6(3x-1)-2x=2(2x-5) | | n+12.1=-4.3 | | 4z+5=-27 | | 4x(5x-2)(3x-8)=0 | | 3.27x+26.16=52.32 | | 3(p+2)=30 | | 10c+5=45 | | 3.52x+9=12.3904+3x | | w^2+12w+81=0 | | 35x-5y=7.7 | | |x-5|=3 | | 3x^2-5x+12x-20=0 | | -5y+8=8-5y-12 | | 15=3u | | x^3-5x+9x-45=0 | | 2z-4z=4 | | 11q+5=49 | | 2=2x+b | | -10y=-8x+14 | | 111111122222333366655444778*1212121212121212=9999999999999999999999999992 | | 543216845614845614564654d*54151561231651325445123141234=97812348521951215132156 | | 3(a-5)=40.8 |

Equations solver categories